2018
DOI: 10.1101/473975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shared striatal activity in decisions to satisfy curiosity and hunger at the risk of electric shocks

Abstract: 1Curiosity is often portrayed as a desirable feature of human faculty. However, curiosity 2 may come at a cost that sometimes puts people in a harmful situation. Here, with a set of 3 behavioural and neuroimaging experiments using stimuli that strongly trigger curiosity (e.g., 4 magic tricks), we examined the psychological and neural mechanisms underlying the irresistible 5 lure of curiosity. We consistently demonstrated that across different samples, people were indeed 6 willing to gamble, subjecting thems… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 112 publications
(114 reference statements)
0
7
0
Order By: Relevance
“…Consistent with this idea, the large majority of fMRI studies on curiosity have reported activation in the ACC [5,18,23,48,49]. For example, whole-brain analyses demonstrate enhanced ACC activation elicited by high-compared with low-curiosity trivia questions [5,18] and by high compared with low perceptual uncertainty about an upcoming scene image [23].…”
Section: Information-based Prediction Errors: a Potential Role Of The Anterior Cingulate Cortexmentioning
confidence: 85%
See 3 more Smart Citations
“…Consistent with this idea, the large majority of fMRI studies on curiosity have reported activation in the ACC [5,18,23,48,49]. For example, whole-brain analyses demonstrate enhanced ACC activation elicited by high-compared with low-curiosity trivia questions [5,18] and by high compared with low perceptual uncertainty about an upcoming scene image [23].…”
Section: Information-based Prediction Errors: a Potential Role Of The Anterior Cingulate Cortexmentioning
confidence: 85%
“…To measure different degrees of curiosity during a state of curiosity, most studies have relied on participants' self-reported subjective curiosity ratings [5,15,16,23,26,27]. Other studies have operationalized curiosity in a more objective manner by measuring willingness to wait for an answer [3,4,6] or to sacrifice rewards (e.g., water in nonhuman primate studies, limited tokens or money in humans) [3,20,71] or by giving participants a choice of which stimuli they would like to experience [48,49,89]. In general, the available evidence suggests that subjective curiosity ratings positively correlate with objective curiosity measures that implicitly test curiosity via willingness to sacrifice scarce resources [3,4,6].…”
Section: Curiosity Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Loewenstein (1994) also argued that the awareness of knowledge gaps shifts people's attention to the lack of knowledge, and this aversive feeling of deprivation is the driving force of people's curious behavior (i.e., loss aversion). One of the reasons why this idea has attracted popularity is that it can explain strong seductive power of curiosity, which sometimes lead people to make irrational decisions (e.g., Hsee and Ruan 2016;Lau et al 2018;Oosterwijk 2017). However, this idea is still controversial and empirical evidence is not conclusive (Ruan et al 2018;Silvia 2006).…”
Section: Curiosity As An Aversive Statementioning
confidence: 99%